Emergency Management of Traumatic Spinal Cord Injuries - Abdul Azeez, Mohammed Maan; Moscote-Salazar, Luis Rafael; Alcala-Cerra, Gabriel; García-Ballestas, Ezequiel; Bustos-Salazar, Diego; Satyarthee, Guru Dutta; Agrawal, Amit (Indian Journal of Neurotrauma, 2020)
Spinal cord trauma constitutes one of the main causes of mortality and morbidity in young adults around the world, with an estimated 2 to 3 new cases for every 100,000 population. Road traffic accidents, falls from high heights, sports injuries, and violent actions are common causes of spinal cord injuries. There is no “gold standard” for the diagnosis of spinal cord traumatic injuries; however, the rational use of conventional radiologic test, computed tomography scan, and magnetic resonance imaging (MRI) will allow to identify almost all clinically relevant injuries. MRI is recommended according to surgeon’s criteria, who after evaluating the specific characteristics of the injury will determine its usefulness. Therapeutic strategies need to be directed to maintain airway, breathing and circulation, maintenance of mean arterial pressure prevention of hypotension, and assessment of other associated injuries. Intensive treatment must be focused on the prevention and management of ventilatory and cardiovascular abnormalities related to muscle weakness and loss of autonomic innervation.
Keywords: spinal cord injury; spinal cord; emergency management